Molecular Mechanisms of the Generation and Accumulation of Gas at the Interface - Zhao, Zhigao (Langmuir : the ACS journal of surfaces and colloids, 2024)
Gas-evolving reactions are widespread in chemical and energy fields. However, the generated gas will accumulate at the interface, which reduces the rate of gas generation. Understanding the microscopic processes of the generation and accumulation of gas at the interface is crucial for improving the efficiency of gas generation. Here, we develop an algorithm to reproduce the process of catalytic gas generation at the molecular scale based on the all-atom molecular dynamics simulations and obtain the quantitative evolution of the gas generation, which agrees well with the experimental results. In addition, we demonstrate that under an external electric field, the generated gas molecules do not accumulate at the electrode surface, which implies that the electric field can significantly increase the rate of the gas generation. The results suggest that the external electric field changes the structure of the water molecules near the electrode surface, making it difficult for gas molecules to accumulate on the electrode surface. Furthermore, it is found that gas desorption from the electrode surface is an entropy-driven process, and its accumulation at the electrode surface depends mainly on the competition between the entropy and the enthalpy of the water molecules under the influence of the electric field. These results provide deep insight into gas generation and inhibition of gas accumulation